SETING ALAMI SEBAGAI SARANA ANAK UNTUK MENGATASI TEKANAN LINGKUNGAN DI KAMPUNG KOTA - Sativa, Sativa; Setiawan, Bakti; Wijono, Djoko; Adiyanti, MG (Jurnal Arsitektur Komposisi, 2017)
Abstract: Nowadays, the majority of Indonesian people live in the dense urban kampungs. Some of those kampungs laid on the riverside, as a marginal area -- due to their low economic value of the land. They have specific conditions especially on the limitation of infrastructures and facilities for children activities in the settlement area. This research is a part of my dissertation paper, which aims to gain how children (mainly school-age children) coping with such condition. This study is a qualitative exploratory research, meanwhile, observation and interview were used as collecting data methods. Kampung Ngampilan in Yogyakarta, Indonesia, was chosen as a case area, because of its unique characteristics: located on the riverside of Winongo River, had a high density, and most people have low economics. As the result, this study found that natural setting, especially river area and its surrounding vegetation, is a focus location for children to release live stress in their settlement, due to two space aspects: thermal comfort and visual comfort. This condition was triggered by the limited area of their house so that the children prefer to go out from their house especially after attending school in the afternoon. This results will be useful as a reference for urban kampung planning, especially in riverfront area.Keywords: children, kampung, environmental press, natural settingAbstrak: Mayoritas penduduk kota Indonesia tinggal di kampung berkepadatan tinggi. Sebagian dari kampung -kampung berada di bantaran sungai sebagai salah satu area kota yang dianggap marginal karena nilai ekonomi lahan rendah. Kampung-kampung umumnya berkondisi khas dan memiliki keterbatasan infrastruktur termasuk fasilitas untuk kegiatan anak-anak di permukiman. Studi ini merupakan bagian dari disertasi penulis, yang bertujuan mengetahui bagaimana anak-anak (terutama anak usia sekolah dasar) menghadapi tekanan lingkungan. Kampung Ngampilan dipilih karena merupakan kampung kota yang sangat padat, terletak di tepi sungai, berkontur curam, dan warganya termasuk kelompok ekonomi menengah ke bawah. Kajian ini menggunakan metode kualitatif eksploratif, dan penggalian data dilakukan dengan metode observasi lapangan dan wawancara. Penelitian menemukan, seting alami kampung, khususnya sungai dan vegetasi di sekitarnya, merupakan area pilihan utama anak bermain, karena memiliki dua aspek kenyamanan, yaitu kenyamanan termal dan kenyamanan visual. Pilihan anak-anak dipicu oleh kondisi rumah mereka yang sempit, sehingga mereka lebih memilih keluar rumah sepulang sekolah atau sore hari. Temuan ini dapat menjadi acuan bagi pengembangan kampung kota Indonesia yang lebih kondusif untuk anak, khususnya kampung tepi sungai.Kata kunci: seting alami, tekanan lingkungan, kampung kota, anak